A PA composition and a method for preparing the same

CN122686112APending Publication Date: 2026-09-04KINGFA SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610645681.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-12
Publication Date
2026-09-04

AI Technical Summary

Technical Problem

然而现有的PA材料一旦暴露在湿热环境下其绝缘效果就会大幅下降,出现电流泄漏,尤其是在PA材料薄壁化设计的情况下,甚至可能出现绝缘失效的情况;另一方面,现有的PA材料为了保障阻燃性能,会在产品中引入含卤阻燃剂,然而在长期处于湿热环境中,含卤阻燃剂会逐渐出现自由基分解的问题,消耗阻燃活性成分,材料的阻燃性能会加速劣化,造成使用危险

Benefits of technology

[0043] The PA composition of the present invention, due to the selection of an anti-current leakage agent, can effectively protect the electrodes under energized conditions from external factors, resulting in low current leakage. At the same time, the product has good flame retardant stability and can still achieve high insulation and flame retardant effects even after treatment in a humid and hot environment. Therefore, it is very suitable for electrode protection components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a PA composition and a preparation method thereof, and belongs to the technical field of high polymer materials. The PA composition can effectively improve the current leakage prevention property of a product in a hot and humid environment, realizes good insulation effect, and guarantees long-term flame retardation of the product in the hot and humid environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, specifically to a PA composition and its preparation method. Background Technology

[0002] PA (polyamide) materials are widely used in fields such as electronics and transportation due to their solvent resistance, processability, and excellent mechanical strength. However, with the iterative upgrades of electronic and electrical products, the performance requirements for PA materials are gradually increasing. For example, in relay components, PA materials are in direct contact with metal electrodes, and the current leakage problem under energized conditions needs to be considered. However, the insulation effect of existing PA materials will decrease significantly when exposed to humid and hot environments, resulting in current leakage, especially in the case of thin-walled PA materials, which may even lead to insulation failure. On the other hand, in order to ensure flame retardant performance, existing PA materials will introduce halogenated flame retardants into the products. However, in long-term humid and hot environments, halogenated flame retardants will gradually undergo free radical decomposition, consuming the flame-retardant active ingredients, accelerating the deterioration of the material's flame retardant performance, and causing safety hazards. Summary of the Invention

[0003] Based on the deficiencies of existing technologies, the purpose of this invention is to provide a PA composition that, by introducing a metal compound and a compounded flame retardant synergist as synergistic components into a product containing a halogenated flame retardant, can not only effectively improve the product's current leakage prevention in humid and hot environments and achieve good insulation effects, but also ensure that the product still has long-lasting flame retardancy when used in humid and hot environments, resulting in excellent overall performance.

[0004] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A PA composition comprising the following components in parts by weight: 100 parts PA66 resin, 20-40 parts halogenated flame retardant, 18-25 parts inorganic flame retardant synergist, 35-75 parts glass fiber, and 3-6 parts anti-current leakage agent. The current leakage inhibitor comprises a metal compound, wherein the band gap of the metal compound is ≥3eV and the average particle size is 1~5μm; The inorganic flame retardant synergist includes zinc borate and antimony white, with a mass ratio of (1~6):1.

[0005] Existing PA materials generally exhibit good insulation properties in a dry state. Therefore, when applied to protective materials for electrodes, they can achieve good insulation protection without current leakage. However, once the working environment changes to a humid and hot environment, PA materials will gradually show a trend of weakening insulation, especially when these materials are designed with thin-walled dimensions. In severe cases, insulation failure and the risk of current leakage may occur. On the other hand, in order to ensure that PA materials have good flame retardant properties, existing products often introduce halogenated flame retardants. However, these flame retardants will decompose to a certain extent under humid and hot conditions, which will lead to a gradual deterioration or even failure of flame retardant performance during operation. To address the issue of insulation and flame retardant degradation in existing PA materials under humid and hot environments, the present invention incorporates a halogenated flame retardant PA composition product that also includes an anti-current leakage agent and a compounded inorganic flame retardant synergist. Metal compounds with a band gap of 3 eV or higher are selected as the anti-current leakage agent. With glass fiber as the inorganic skeleton component and specific size limitations on these metal compounds, they can be uniformly dispersed in the matrix resin of the composition, effectively blocking the electronic conduction characteristics of the product's internal and external layers, thus maintaining good insulation properties even under humid and hot conditions. Furthermore, zinc borate and antimony white are introduced as compounded flame retardant synergists; the former has… High flame retardant synergy enhances the flame retardant performance of the product. As an inorganic component, it exhibits relatively high inertness in humid and hot environments, preventing the decomposition of halogenated flame retardants and avoiding any impact on the insulation and protection effect of anti-current leakage agents. The latter, as an amphoteric compound, can react with some of the free radicals generated by the decomposition of halogenated flame retardants, stabilizing the pH of the product system. Therefore, under specific proportions, in addition to exhibiting synergistic flame retardant properties, it can also inhibit the interference of halogenated flame retardant decomposition on other components, especially anti-current leakage agents. Ultimately, it balances improving both the insulation and flame retardant effects of the product in humid and hot environments. After humid heat treatment, the product exhibits low current leakage under energized conditions, while maintaining excellent flame retardant performance.

[0006] However, if the proportion of the compound flame retardant synergist introduced is inappropriate, it will greatly affect the flame retardant performance of the product. Especially in humid and hot environments, the flame retardant performance of the product will not meet the expected standard requirements, and may even affect the product's anti-current leakage performance.

[0007] In some embodiments, the halogenated flame retardant is in the range of 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts, 37 parts, and 40 parts by weight, or any two of these values; the glass fiber is in the range of 35 parts, 40 parts, 45 parts, 50 parts, 60 parts, and 75 parts by weight, or any two of these values; the inorganic flame retardant synergist is in the range of 18 parts, 20 parts, 22 parts, 23 parts, 24 parts, and 25 parts by weight, or any two of these values; and the anti-current leakage agent is in the range of 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, and 6 parts by weight, or any two of these values.

[0008] In some embodiments, the mass ratio of the inorganic flame retardant synergist to the anti-current leakage agent is 1:(0.1~0.35). More preferably, the mass ratio of the inorganic flame retardant synergist to the anti-current leakage agent is 1:(0.15~0.25). More preferably, the PA composition comprises the following components in parts by weight: 100 parts PA66 resin, 25-37 parts halogenated flame retardant, 20-24 parts inorganic flame retardant synergist, 40-70 parts glass fiber, and 3.5-5.5 parts anti-current leakage agent.

[0009] When the above weight ratio is selected for the compounding of PA components, the product can achieve better current leakage resistance and flame retardant properties.

[0010] More preferably, the PA66 resin has a mass content of ≥40wt% in the PA composition.

[0011] More preferably, the glass fiber content in the PA composition is ≥15wt%, and even more preferably 15~45wt%.

[0012] In the technical solution of the present invention, the product can achieve excellent tensile strength with a high proportion of matrix resin, and has strong insulation properties when used as a protective component for energized electrodes. It does not need to consider the application limitations of existing products based on the amount of matrix resin and glass fiber, and is highly practical.

[0013] Preferably, the PA66 resin has a relative viscosity of 2.1 to 3.8 at 23°C according to ISO307-2007.

[0014] Preferably, the metal compound includes at least one of metal oxides and metal sulfides.

[0015] Specifically, the metal compound may be at least one of zinc compound, manganese compound, and titanium compound.

[0016] For example, when the metal compound is a zinc compound, it can be zinc oxide or zinc sulfide; when the metal compound is a manganese oxide, it can be manganese oxide; when the metal compound is a titanium compound, it can be titanium dioxide, etc., but it is not limited to these. Those skilled in the art can also select other metal compounds that conform to the definition of this invention according to actual needs.

[0017] Preferably, the band gap of the metal compound is 3 to 4 eV.

[0018] More preferably, the band gap of the metal compound is a range of one or any two of the following: 3eV, 3.1eV, 3.2eV, 3.3eV, 3.4eV, 3.5eV, 3.6eV, 3.8eV, and 4eV.

[0019] More preferably, the band gap of the metal compound is 3~3.6 eV.

[0020] The band gap of the metal compound described in this application can be tested by photoluminescence spectroscopy. The wavelength of the characteristic fluorescence peak of the sample when photons are emitted is confirmed by a spectrometer and substituted into E=hc / λ for calculation, where E is the band gap, h is Planck's constant, c is the speed of light, and λ is the wavelength.

[0021] Preferably, the average retained particle size of the metal compound is 1 μm to 5 μm.

[0022] More preferably, the retained average particle size of the metal compound is a range of one or any two of 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, and 5 μm.

[0023] More preferably, the band gap of the metal compound is ≥3.2 eV and the average particle size is 2 μm to 4 μm.

[0024] A larger bandgap in the metal compound can effectively improve the insulation performance of the product. However, the particle size of the material in the PA composition will affect the dispersion uniformity of the product. In particular, the product also contains zinc borate and antimony white, which also exist in particulate form and are dispersed together with the metal compound in the matrix resin and glass fiber skeleton. If the particle dispersion is uneven, the effect of blocking electron conduction in the product will be uneven. Therefore, it needs to be strictly controlled. When the lower limit of the bandgap of the metal compound is further increased to the above-mentioned range, and the upper and lower limits of the retained particle size are optimized, the dispersion uniformity of the particles can be effectively improved. Moreover, the compatibility with the distribution of flame retardant synergists in the product is better, and the two will not weaken each other.

[0025] It should be noted that the retained average particle size of the metal compound refers to the average retained particle size of the metal compound in the prepared PA composition. Specific testing methods can be various, including but not limited to directly cutting the PA composition into transmission electron microscopy test sections, identifying metal compound particles at 20kx magnification, screening 100 particles, measuring the particle size using Nano Measure software, and calculating the average value. If the identified metal compound is of a type with high high-temperature chemical inertness, such as titanium dioxide, the PA composition can be directly placed in a muffle furnace for pyrolysis at 500℃, the resulting ash can be dispersed with ethanol, and the metal compound particles can be observed under a two-dimensional optical microscope, screening 100 particles, measuring the particle size, and calculating the average value.

[0026] Meanwhile, the average particle size of the metal compound can be controlled by those skilled in the art using metal compounds with different original particle sizes, or it can be controlled by adjusting parameters such as different feed inlets or screw speeds during the preparation of the PA composition, without any special restrictions.

[0027] Preferably, the average diameter of the retained glass fiber is 9~13μm and the average length is 200~300μm.

[0028] It should be noted that the average retained diameter and average retained length of the glass fibers mentioned in this invention refer to the average retained diameter and length of the glass fibers in the prepared PA composition. Specific testing methods can be varied, including but not limited to directly cutting the PA composition into transmission electron microscopy (TEM) sections, identifying the glass fibers at 20kx magnification, selecting 50 fibers, measuring the diameter and length using Nano Measure software, and calculating the average value. Alternatively, the PA composition can be directly pyrolyzed in a muffle furnace at 500°C, the resulting ash dispersed in ethanol, and confirmed by optical microscopy. At least 50 glass fiber samples are statistically analyzed under a two-dimensional microscope, and the average value is calculated to obtain the average retained diameter and average retained length of the glass fibers. In some embodiments, the mass ratio of zinc borate to antimony white is one or any two of the following: 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1.

[0029] More preferably, the mass ratio of zinc borate to antimony white is (2~4):1.

[0030] As mentioned above, the inorganic flame retardant synergist composed of zinc borate and antimony white can not only maintain the flame retardant performance of the product after humid heat treatment, but also, because these two substances can work together with the anti-current leakage agent to fully exert their insulating properties in humid heat environment and block current conduction, when the ratio of the two is preferably within the above range, the product not only has a lower degree of current leakage after being placed in humid heat environment for a long time, but also has better flame retardant properties.

[0031] More preferably, the average retained particle size of the zinc borate is 5-10 μm, and the average retained particle size of the antimony white is 5-10 μm.

[0032] In some embodiments, the halogenated flame retardant includes at least one of brominated flame retardants and chlorinated flame retardants.

[0033] More preferably, the halogenated flame retardant is a brominated flame retardant, and may be, but is not limited to, at least one of organic bromides and brominated organic polymers, specifically including at least one of polybrominated diphenyl ethers, hexabromocyclododecane, decabromodiphenyl ethane, octabromoether, tetrabromobisphenol A, brominated polystyrene, and brominated polyethylene.

[0034] In some embodiments, the PA composition also includes an antioxidant.

[0035] More preferably, the antioxidant is present in a weight ratio of 0.2 to 1 part.

[0036] More preferably, the antioxidant includes at least one of hindered phenolic antioxidants, phosphite antioxidants, and hindered amine antioxidants.

[0037] When the PA composition described in this invention is selected as the electrode protection component, those skilled in the art can introduce a small amount of antioxidant to improve the product's oxidation resistance without affecting the product's insulation and flame retardant properties, which is not limited here.

[0038] Preferably, the components of the PA composition may include, but are not limited to, antibacterial agents, lubricants, etc. Based on the needs of those skilled in the art for processing or actual use of the product, other types of functional additives may be added without affecting the expected performance of the product. For example, the above-mentioned additives can improve the antibacterial ability and demolding success rate of the product without affecting the characteristic performance of the product. That is, the description of the product components in the technical solution of the present invention is not a limitation on the types of components.

[0039] Another object of the present invention is to provide a method for preparing the PA composition, comprising the following steps: The components are added to a screw extruder for melt extrusion granulation to obtain the PA composition.

[0040] Preferably, the temperature zones of the screw extruder are set as follows: Zone 1 180~200℃, Zone 2 250~270℃, Zone 3 260~280℃, Zone 4 270~280℃, Zone 5 270~280℃, Zone 6 270~280℃, Zone 7 260~270℃, Zone 8 260~270℃, and Zone 9 260~270℃, and the screw speed is 200~400 rpm.

[0041] Another object of the present invention is to provide the use of the PA composition in the preparation of electrode protection components.

[0042] Another object of the present invention is to provide an electrode protection component comprising the PA composition described herein.

[0043] The PA composition of the present invention, due to the selection of an anti-current leakage agent, can effectively protect the electrodes under energized conditions from external factors, resulting in low current leakage. At the same time, the product has good flame retardant stability and can still achieve high insulation and flame retardant effects even after treatment in a humid and hot environment. Therefore, it is very suitable for electrode protection components.

[0044] The beneficial effects of this invention are that it provides a PA composition, which, by introducing a metal compound and a compounded flame retardant synergist as synergistic components into a product containing a halogenated flame retardant, can not only effectively improve the product's current leakage prevention in humid and hot environments and achieve good insulation effects, but also ensure that the product still has long-lasting flame retardancy when used in humid and hot environments, resulting in excellent overall performance. Detailed Implementation

[0045] To better illustrate the purpose, technical solution, and advantages of this invention, the invention will be further described below with reference to specific embodiments and comparative examples. The purpose of this description is to provide a detailed understanding of the invention, not to limit its scope. All other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of this invention. Unless otherwise specified, the experimental reagents and instruments involved in the implementation of this invention are commonly used reagents and instruments.

[0046] Examples 1-13 Examples of the PA composition of the present invention are shown in Table 1.

[0047] The method for preparing the PA composition includes the following steps: The components are mixed evenly, and then melt-extruded and granulated in a twin-screw extruder to obtain the PA composition.

[0048] During melt extrusion of the component, the temperature zones of the screw extruder are set as follows: Zone 1 190℃, Zone 2 260℃, Zone 3 270℃, Zone 4 275℃, Zone 5 275℃, Zone 6 275℃, Zone 7 270℃, Zone 8 270℃, Zone 9 270℃, and the screw speed is 400 rpm.

[0049] In Example 8, the screw speed was adjusted to 500 rpm during the preparation of the PA composition.

[0050] Comparative Examples 1-9 The only difference between each comparative example and Example 1 is the type and ratio of components, as shown in Table 2.

[0051] In the components described in each embodiment and comparative example, The PA66 resin 1 is EP122, produced by Huafeng Group Co., Ltd., with a relative viscosity of 2.2 at 23°C; The PA66 resin 2 is T37, produced by Huafeng Group Co., Ltd., with a relative viscosity of 3.7 at 23°C; The current leakage inhibitor 1 is a commercially available zinc sulfide with an average particle size of 3.1 μm and a band gap of 3.6 eV; The current leakage inhibitor 2 is commercially available zinc oxide with an average particle size of 3.8 μm and a band gap of 3.2 eV; The current leakage inhibitor 3 is commercially available zinc oxide with an average particle size of 2.2 μm and a band gap of 3.2 eV; The current leakage inhibitor 4 is commercially available zinc oxide with an average particle size of 4.7 μm and a band gap of 3.2 eV; The current leakage inhibitor 5 is commercially available manganese oxide with an average particle size of 3.3 μm and a band gap of 3.6 eV; The current leakage inhibitor 6 is commercially available titanium dioxide with an average particle size of 3.4 μm and a band gap of 3.2 eV; The current leakage inhibitor 7 is commercially available manganese sulfide with an average particle size of 3.3 μm and a band gap of 3 eV; The current leakage inhibitor 8 is a commercially available molybdenum disulfide with an average particle size of 3.5 μm and a band gap of 1.2 eV; The current leakage inhibitor 9 is a commercially available zinc sulfide with an average particle size of 1 μm and a band gap of 3.6 eV; The current leakage inhibitor 10 is a commercially available zinc sulfide with an average particle size of 6 μm and a band gap of 3.6 eV; The halogenated flame retardant 1 is commercially available brominated polystyrene; The halogenated flame retardant 2 is commercially available decabromodiphenyl ethane; The glass fiber 1 is ECS10-03-568H produced by Jushi Group, with an average diameter of 10μm and an average length of 2900μm; The glass fiber 2 is ECS13-03-534A produced by Jushi Group, with an average diameter of 13μm and an average length of 3100μm; The antioxidant is commercially available hindered phenolic antioxidant 1098.

[0052] The inorganic flame retardant synergist 1 is commercially available zinc borate with an average particle size of 8 μm. The inorganic flame retardant synergist 2 is commercially available antimony white with an average particle size of 6μm; The flame retardant synergist 3 is ADINS CLAY 80T, a silicate flame retardant synergist produced by Shanghai Zhuangjing Chemical. The flame retardant synergist 4 is commercially available sepiolite with an average particle size of 5.5 μm; The flame retardant synergist 5 is commercially available iron oxide with an average particle size of 6 μm; Unless otherwise specified, all components and raw materials used in the embodiments and comparative examples of this invention are commercially available, and the same type of components and raw materials are used in each parallel experiment.

[0053] The test methods for the retained average particle size of the metal compound and the retained average length and diameter of the glass fiber are as described above. Specifically, the PA composition is cut into transmission electron microscopy (TEM) test sections. At 20kx magnification, elemental analysis is used to identify the metal compound particles, and 100 particles are screened. The particle size is measured using Nano Measure software, and the average value is calculated to confirm the retained average particle size of the metal compound. At 20kx magnification, glass fibers are identified, and 50 fibers are screened. The diameter and length of the fibers are measured using Nano Measure software, and the average value is calculated to obtain the retained average length and retained average diameter of the glass fiber. These methods will not be elaborated further here.

[0054] Table 1 Table 2 To verify the performance of the PA composition described in this invention, the products prepared in each example and comparative example were subjected to the following performance tests, with the specific steps as follows: (1) The products obtained in each embodiment and comparative example were injection molded into test specimens of 100×100mm and 1mm thickness. Then, they were placed in hot water at 95°C and left to stand for 8 hours. After that, they were taken out and left to stand at room temperature for 8 hours. The leakage current was directly tested using an insulation resistance meter. The voltage during the test was 2.5kV. At the same time, parallel comparison specimens were set up. The comparison specimens were the same size and the leakage current was directly tested in a dry state without any treatment. (2) The products obtained from each embodiment and comparative example were subjected to flame retardancy test according to UL94-2023 standard. The test thickness was 1.5 mm. Before the test, the samples were placed in hot water at 95°C for 8 hours and then taken out and placed at 60°C for 24 hours before the test.

[0055] The test results are shown in Tables 3 and 4.

[0056] Table 3 Table 4 As can be seen from Tables 3 and 4, the PA composition of the present invention has ideal insulation properties. The leakage current does not exceed 0.1mA when tested after damp heat treatment. At the same time, the flame retardant rating of the product can still reach V-1 or above after damp heat treatment, and the overall performance is excellent.

[0057] In contrast, the product described in Comparative Example 1 did not incorporate an anti-current leakage agent, yet exhibited a high leakage current in the dry state. This demonstrates that the high bandgap metal compound described in this invention, when used as an anti-current leakage agent, provides excellent electrical insulation. While Comparative Example 2, even with a metal compound possessing certain insulating properties as a functional component, achieved low current leakage in the dry state, it still failed to meet standards after damp heat treatment if the bandgap did not meet the limits set by this invention. Furthermore, as seen in Examples 1, 5-10, and Comparative Examples 3 and 4, when a high bandgap metal compound is selected as a functional component, the retained particle size and dispersion uniformity vary. Excessively large or small retained particle sizes of the metal compound can weaken the anti-current leakage effect of the PA composition after damp heat aging. Conversely, when the bandgap of the metal compound is ≥3.2 eV and the average retained particle size in the composition is 2 μm to 4 μm, the anti-current leakage effect of the product is superior both in the dry state and after damp heat aging.

[0058] In addition, the combination of flame retardant synergists in the PA composition of the present invention not only affects the flame retardant rating of the product after damp heat aging, but if the types used are inappropriate, as shown in Comparative Examples 7-9, the current leakage prevention effect of the product may also fail to meet the standard. As can be seen from Examples 1, 11-13 and Comparative Examples 5-6, when zinc borate and antimony white are used as compound inorganic flame retardant synergists in the product, if the ratio is not in the range of (1-6):1, the flame retardant rating of the product after damp heat aging cannot meet the standard. When the ratio is further preferably in the range of (2-4):1, not only is the flame retardant rating of the product higher after damp heat aging, but the leakage current of the product is also lower, resulting in better overall performance.

[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A PA composition, characterized in that, Includes the following components in parts by weight: 100 parts PA66 resin, 20-40 parts halogenated flame retardant, 18-25 parts inorganic flame retardant synergist, 35-75 parts glass fiber, and 3-6 parts anti-current leakage agent. The current leakage inhibitor comprises a metal compound, wherein the band gap of the metal compound is ≥3eV and the average particle size is 1~5μm; The inorganic flame retardant synergist includes zinc borate and antimony white, with a mass ratio of (1~6):

1.

2. The PA composition according to claim 1, characterized in that, The relative viscosity of the PA66 resin at 23°C is 2.1~3.

8.

3. The PA composition according to claim 1, characterized in that, The metal compound includes at least one of metal oxides and metal sulfides.

4. The PA composition according to claim 1, characterized in that, The band gap of the metal compound is ≥3.2 eV and the average particle size is 2 μm to 4 μm.

5. The PA composition according to claim 1, characterized in that, The average diameter of the retained glass fibers is 9~13μm, and the average length is 200~300μm.

6. The PA composition according to claim 1, characterized in that, The mass ratio of zinc borate to antimony white is (2~4):

1.

7. The PA composition according to claim 1, characterized in that, The halogenated flame retardant includes at least one of brominated flame retardants and chlorinated flame retardants; preferably, the halogenated flame retardant is a brominated flame retardant, which includes at least one of organic bromides and brominated organic polymers.

8. The PA composition according to claim 1, characterized in that, The PA composition also includes an antioxidant; the antioxidant is present in parts by weight of 0.2 to 1 part.

9. A method for preparing the PA composition according to any one of claims 1 to 8, comprising the following steps: The components are added to a screw extruder for melt extrusion granulation to obtain the PA composition.

10. An electrode protection component, characterized in that, Includes the PA composition according to any one of claims 1 to 8.